Evaluation of the Implementation of the Independent Curriculum in PJOK at Public Junior High Schools in Depok Sub-district, Sleman Regency - Subandiyo, Subandiyo; Ngatman, Ngatman; Akbar, Claudio Fadia (Indonesian Journal of Sport Management, 2025)
Background: The curriculum is everything that includes the learning experience that students go through and affects the development of their personality which is obtained not only from the school environment but also from the family and community environment. Purpose: This study aims to evaluate the implementation of Merdeka Curriculum in PJOK learning using the CIPP (Context, Input, Process, and Product) model in State Junior High Schools in Depok District, Sleman. Methods: The research method used is the CIPP (Context, Input, Process, and Product) model. The research population involved PJOK Teachers, Principals and supervisors who served in State Junior High Schools in Depok District, Sleman and students from five schools. Data were collected using observation guidelines, interview guidelines, questionnaires, and documentation. Data analysis techniques in this study are quantitative and qualitative descriptive analysis techniques in accordance with the evaluation model. Results: The results showed that the evaluation of the context of implementing the Merdeka Curriculum was 3.22 (good). The input evaluation of the implementation of the PJOK Merdeka Curriculum is 3.23 (good). Evaluation of the process of implementing the PJOK Independent Curriculum is 2.92 (good). Product evaluation of the implementation of the PJOK Merdeka Curriculum is 3.23 (good). Evaluation of the implementation of the Independent Curriculum in PJOK learning is 3.15 (good). Conclusion: Thus, it can be concluded that the evaluation of the implementation of the Merdeka Curriculum in PJOK learning at SMP N in Depok sub-district has gone well.  Implications and Recommendation: After evaluating the context, input, process, product, it can be decided that the implementation of Merdeka Curriculum in learning PJOK in Depok sub-district needs some improvements to achieve more optimal results.